Kontekstualisasi Pemahaman Hadis - Muhammad Rizqi; Ahmad Deski; Muhammad Ikhwan (IAIN Batusangkar, 2023)
This research aims to reveal the meaning of the hadiths of the Prophet Muhammad by explaining the text of the hadith along with an understanding of the hadith in accordance with the current context without departing from the meaning of its content. This research is library research using the content analysis method, approaching hadith texts and analyzed using related hadith explanation. This research found that every hadith of the Prophet Muhammad did not always correspond to the textual editorial because when he conveyed the hadith, he was sometimes in his position as an apostle, judge, mufti and as an ordinary human being. Sometimes some hadiths are intended for certain people, places and times, so it is necessary to study the asbabul wurud and the socio-historical conditions of society at the time of the hadith narration, so that the understanding of modern situations and conditions becomes different, in accordance with the information of the hadith narrating scholars.